Village Government Policies to Unravel the Failure in handling Stunting(Case study of Candiyasan Village, Wonosobo Regency) - Mahmud, Insan (Unnes Political Science Journal, 2024)
The prevalence of stunting in 2021 according to the Indonesian Infant Nutrition Survey (SSGBI) was 24.4%. This figure still exceeds the WHO limit of 20%. The prevalence of stunting cases in Wonosobo Regency touched 10.49 percent and Candiyasan Village is the locus of stunting in Kertek District. This study aims to identify the factors causing the high stunting rate in Candiyasan Village and its relation to the extreme poverty rate, which is also high in Kertek Sub-district. The method used is descriptive qualitative method according to the results of interviews as primary data and literacy data as secondary data. The results show that stunting cases are caused by several factors, including: high rates of early marriage, pregnant women's awareness of the importance of checking nutritional fulfillment during pregnancy, nutritional fulfillment patterns, family food security, and poverty. The majority of stunting toddlers come from poor families.